The incidence of hyperkalemia in patients with secondary hyperparathyroidism after ultrasound-guided radiofrequency ablation vs. parathyroidectomy - Ren, Mian; Liu, Yueming; Lin, Bo; Zou, Wenli; Zhu, Bin; Wu, Juan (Frontiers in Medicine, 2025)
IntroductionThe aim of our study was to compare the incidence of hyperkalemia in maintenance dialysis patients with secondary hyperparathyroidism(SHPT) after parathyroidectomy(PTX) or ultrasound-guided radiofrequency ablation(RFA), and to explore the risk factors and the best preoperative serum potassium threshold.MethodsWe defined hyperkalemia as serum potassium >5.30 mmol/L. Two operation methods were analyzed in subgroups, and the differences in demographic parameters, operation situation and perioperative laboratory indicators were compared between the two groups.ResultsA total of 154 maintenance dialysis patients were included, of which 91 patients received PTX and 63 patients received RFA. 53 patients (34.4%) developed postoperative hyperkalemia. Patients in hyperkalemia group had higher preoperative serum potassium, phosphorus, hemoglobin and 25-hydroxyvitamin D level (p < 0.05). It seemed that males were more prone to suffer hyperkalemia than females, but there was no statistically difference (40.9% vs. 25.8%, p = 0.05). The occurrence of hyperkalemia after the operation was obviously higher in hemodialysis patients. Logistic regression analysis showed that preoperative serum potassium level (OR = 3.269, 95%CI 1.638–6.534, p = 0.001) and PTX (OR = 18.119, 95%CI 5.716–57.438, p < 0.01) were independent risk factors for predicting postoperative hyperkalemia. According to ROC curve analysis, the optimal cutoff value for preoperative serum potassium was 4.66 mmol/L, with a sensitivity of 46.8% and a specificity of 86%.ConclusionHyperkalemia after invasive treatment in patients with severe SHPT was common, and the incidence of hyperkalemia after PTX was significantly higher than that after RFA. Hemodialysis patients were more prone to hyperkalemia, which was related to the preoperative serum potassium level.